Disentangling the Effects of Ocean Carbonation and Acidification on Elemental Contents and Macromolecules of the Coccolithophore Emiliania huxleyi - Xie, Emei; Xu, Kui; Li, Zhengke; Li, Wei; Yi, Xiangqi; Li, Hongzhou; Han, Yonghe; Zhang, Hong; Zhang, Yong (Frontiers in Microbiology, 2021)
Elemental contents change with shifts in macromolecular composition of marine phytoplankton. Recent studies focus on the responses of elemental contents of coccolithophores, a major calcifying phytoplankton group, to changing carbonate chemistry, caused by the dissolution of anthropogenically-derived CO2 into the surface ocean. However, the effects of changing carbonate chemistry on biomacromolecules, such as protein and carbohydrate of coccolithophores are less documented. Here, we disentangled the effects of elevated dissolved inorganic carbon (DIC) concentration (900 to 4930 μmol kg–1) and reduced pH value (8.04 to 7.70) on physiological rates, elemental contents and macromolecules of the coccolithophore Emiliania huxleyi. Compared to present DIC concentration and pH value, combinations of high DIC concentration and low pH value (ocean acidification) significantly increased pigments content, particulate organic carbon (POC) and carbohydrate content, and had less impact on growth rate, maximal relative electron transport rate (rETRmax), particulate organic nitrogen (PON) and protein content. In high pH treatments, elevated DIC concentration significantly increased growth rate, pigments content, rETRmax, POC, particular inorganic carbon (PIC), protein and carbohydrate contents. In low pH treatments, the extents of the increase in growth rate, pigments and carbohydrate content were reduced. Compared to high pH value, under low DIC concentration, low pH value significantly increased POC and PON contents and showed less impact on protein and carbohydrate contents, however under high DIC concentration, low pH value significantly reduced POC, PON, protein and carbohydrate contents. These results showed that reduced pH counteracted the positive effects of elevated DIC concentration on growth rate, rETRmax, POC, PON, carbohydrate and protein contents. Elevated DIC concentration and reduced pH acted synergistically to increase the contribution of carbohydrate–carbon to POC, and antagonistically to affect the contribution of protein–nitrogen to PON, which further shifted the carbon : nitrogen ratio of E. huxleyi.